Analisis Kesulitan Siswa SMP dalam Memecahkan Masalah Statistika Berdasarkan Tahapan Polya - Nursyahidah, Farida; Wardono, Wardono; Mariani, Scolastika; Wijayanti, Kristina (Universitas PGRI Semarang, 2026)
Mathematical problem-solving skills are essential competencies in 21st-century education, particularly in statistics, where students must interpret data, analyze variability, and make informed decisions. However, many students experience significant difficulties when solving statistical problems. This study aims to analyze students' difficulties in solving statistical problems based on Polya's four stages of problem-solving: understanding the problem, developing a plan, implementing the plan, and looking back. This study uses a descriptive qualitative approach with 70 junior high school students in Semarang as subjects selected using a purposive sampling technique. Data were collected through written tests and semi-structured interviews. The findings revealed that students experienced difficulties in solving statistical problems based on Polya's stages were 45% of students were unable to complete the understanding stage, especially in identifying known information and organizing important information needed; 55% of students had difficulties at the planning stage, especially in selecting appropriate statistical procedures; 61% of students still had difficulties at the implementing stage of the plan; and 66% of students still had difficulties at the re-examination stage. This study provides implications for the development of integrated learning designs with real-world contexts and technology that emphasize structured problem-solving processes, thereby improving students' problem-solving abilities.